MEMPERDEBAT WUJÛDIYAH SYEIKH HAMZAH FANSURI (Kajian Hermeneutik atas Karya Sastra Hamzah Fansuri) - Syarifuddin Syarifuddin (Religia, 2010)
This paper is to analyze the causes of different opinions emerge regarding the provision of false labels, zindîq, pantheism, and similar for the teachings of Hamzah Fansuri’s wujûdiyah, so that it should be prior studies in accordance with the nature wujûdiyah itself with Sufi’s taught that institutionalized in the literary works with hermeneutic approach. Further, this research studies on the basis of what scholars have criticized this Sufi‘s teachings wujûdiyah and vice versa, on the basis of what scholars have given their support to this teaching